Effect of methotrexate onsStillbirth, weight of mice embryos and histopathological changes of embryonic liver - Salman, Mohammad O.; Al-Saadi, Rana R.; Al-Ani, Ban T.; Al-Ani, Imad Matloub; Al-Jashamy, Karim (Department of Anatomy, National University of Singapore, 2016)
Methotrexate (MTX) is a folic acid antagonist, which is widely used as a cytotoxic chemotherapeutic agent for malignancies as well as for the treatment of psoriasis, rheumatic diseases and cancer. On another hand, it might cause serious or life-threatening toxicities on liver, lungs, kidney, and immune system. The present study was conducted to assess the harmful effect of the low dose of MTX on the stillbirth, weight of the mice embryos, and to determine the histopathological changes of the embryonic liver during two gestational ages. Thirty mice were divided into to three groups, of 10 pregnant mice each. The fi rst group (G1) was injected low dose of MTX (0.02 mg/kg), at days 4, 5 and, 6 of gestation. The second group (G2) injected by same dose of MTX at days 14, 15 and 16. The third group (G3) served a control group and injected with 0.5 ml of normal saline. Pregnant rats sacrifi ced on gestational day 7 and 17 of gestation. Embryo weight and incidence of intrauterine death were recorded. Twenty mice embryos were fi xed in the Bouin fi xative and processed for histological study. The result showed a signifi cant (P< 0.05) decrease in embryos’ weight at days 7 and a highly signifi cant reduction (P< 0.01) at days17 of gestation compared with control groups. In addition, there was a highly signifi cant increase (P< 0.01) in mortality rate that was observed in the embryos of MTX treated pregnant mice. The histological examination showed fatty changes, degeneration, variability in nuclear size and staining, and necrosis of hepatocytes. These results confi rm that administration of low dose MTX in early pregnancy has teratogenicity effect on liver development.